THE ROLE OF CRITICAL THINKING IN TEACHING READING AND WRITING - Khaydarova Nigora; Ataullayeva Madina (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Critical thinking is crucial for developing reading and writing skills, transforming them into engaging processes. This article explores how it enhances students’ abilities to analyze and synthesize information, emphasizing essential cognitive skills like inference and metacognition. It discusses effective pedagogical strategies and argues that critical thinking is vital for academic success and informed decision-making in today’s complex information landscape.